EFEKTIFITAS POSISI JONGKOK DAN POSISI MIRING KIRI TERHADAP PERCEPATAN KEMAJUAN PERSALINAN KALA I FASE AKTIF PADA IBU INPARTU DI RSUD TALUK KUANTAN - Wiji, Rizki Natia Wiji Natia; Mardia, Ainur; Yuningsih, Silvia Anita (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2020)
Childbirth is a process of opening and thinning of the cervix and the fetus downinto the birth canal. One of the efforts made in order to make the process of childbirth stage 1 active phase smoothly especially for younger pregnant women and primiparous . theywere directed for the position that feels comfortable and helps them to accelarate the opening of the cervix and decrease head.There is also the advantage of squatting position is a natural position during childbrith because it utilizes the force of gravity,while the left tilted position is the blood circulation behind the mother can run smoothly.This study aims to determine the difference between a squat position and leaningto left position to accelerate the progress of the active phase of the first stage ofprimiparous in RSUD Taluk Kuantan.Method: This study uses True experimental research design with the design o wo ptretest-posttest design. The population is all inpartu in RSUD Taluk Kuantan. Samples were selected by purposive sampling technique amounts to 30 people. The research instrument using the partograph.From all of the respondentsin get in as many as 15 getgive position in a squat and oblique position left 15 in give an oblique position left at get all respondents progress childbirth when i phase as many as 13 activite respondents. However statistical test the significance 0,014.In conclusion an oblique position left more effective against the acceleration of progress with the delivery phase when i turned on in mommy inpartu as opposed to the position of squat in rsud taluk kuantan. On advice at RSUD Taluk KuantanÂ  can choose a position at home that is the position of the most effective and speed up progress childbirth kala I. active phase